Pengembangan Model Komunikasi Pelayanan untuk Menghasilkan Kader yang Kreatif dalam Menunjang Keberhasilan Program Bina Keluarga Balita - HASTASARI, CHATIA; PERWITA, ALVIKA HENING (Komunikator, 2014)
One implementation of government policy to build family’s prosperity by increasing the quality of children is realizing The Building of Family and Children under Five Years Program or Bina Keluarga Balita (BKB). BKB activities are organized by cadres of community who volunteer to explain to the target of BKB Program. However, there is a resistance which is the cadres are lack of creativity in implementing community service model. It becomes the main factor why BKB program is not maximal.Service communication model which is used by cadres to deliver the materials is boring and makes the target group bored.Moreover, they lost their motivation to participate in BKB Program. This research applies “research and development” design. This is a research which follows the development programs. Service communication model of BKB cadres is built through systematic stages by applying Focus Group Discussion (FGD) method. In general, this research is done to determine service communication model which is used by the cadres. Furthermore, it also creates a model for the development of service communication in producing more creative cadres which are able to support the success of BKB Program. The result of this research is a service communication model that is able to make cadres more creative in supporting the success of BKB Program. Keywords: Service Communication Model, BKB Program, BKB Cadres